Komunikasi Interpersonal dan Kepuasan Pernikahan pada Pasangan Suami Istri di Kelurahan Limau Mungkur LK. IV, Binjai Barat, Binjai Sumatera Utara - Elisabeth Natalia Tampubolon; Marsya Shalsabila; Amanda Jelita Gulo; Ginda Sar Ulina Manurung; Winida Marpaung; Achmad Irvan Dwi Putra (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of this study was to understanding and examining the connection between Interpersonal Communication and Marital Satisfaction. The research sample was determined to be 127 married couple in Limau Mungkur LK. IV sub district, Binjai Barat, Binjai using purposive sampling technique, with the interpersonal communication and marital satisfaction scales consisting of 30 and 35 items respectively. Data analysis using Pearson Product Moment analysis. The results showed a positive impact and significant relationship between interpersonal communication and marital satisfaction with a correlation coefficient of 0.436 and a significance value of 0.000 (p < 0.05). This means, the higher the interpersonal communication, the higher the married couples marital satisfaction and vice versa. The effective contribution of interpersonal communication to marital satisfaction was 19% and 81% were influenced by factors that were not studied.